Consecutive treatments with photodynamic therapy and nystatin altered the expression of virulence and ergosterol biosynthesis genes of a fluconazole-resistant Candida albicans in vivo - Jordão, Cláudia Carolina [UNESP]; Klein, Marlise Inêz [UNESP]; Carmello, Juliana Cabrini [UNESP]; Dias, Luana Mendonça [UNESP]; Pavarina, Ana Cláudia [UNESP] (Elsevier, 2021)
This investigation assessed the effect of five consecutive daily topical treatments of antimicrobial photodynamic therapy (aPDT), nystatin (NYS), and an association of treatments on a fluconazole-resistant strain of Candida albicans colonizing the tongues of mice. After the last treatments application, colonies of C. albicans were recovered from the tongues and used to determine their fluconazole susceptibility. After 24 hours of the last treatment, the mice tongues were processed to evaluate the expression of C. albicans genes related to the virulence and ergosterol production. The fluconazole susceptibility test yielded a resistance profile similar for all treatment groups and the control group (no treatment). The treatments aPDT, NYS, NYS+aPDT, and aPDT+NYS promoted a reduction in ALS1, EFG1, CAP1, SOD1, SAP1, and LIP3 expression. The expression of HWP1 was higher in the three groups containing nystatin. In contrast, the treatments produced a significative increase in CAT1 gene expression, mainly in the groups in which aPDT was performed. The expression of genes related to ergosterol production was significantly reduced by the treatments evaluated (aPDT, NYS, NYS+aPDT, and aPDT+NYS). Thus, the consecutive topical treatments performed on mice tongues promoted a reduction in the expression of virulence and ergosterol biosynthesis genes of a fluconazole-resistant C. albicans.
Keywords: Antimicrobial photodynamic therapy; Candida albicans; Combined modality therapy; Ergosterol; Gene expression; Virulence